2014
DOI: 10.1177/1355819614546032
|View full text |Cite
|
Sign up to set email alerts
|

Association between market concentration of hospitals and patient health gain following hip replacement surgery

Abstract: ObjectivesTo assess the association between market concentration of hospitals (as a proxy for competition) and patient-reported health gains after elective primary hip replacement surgery.MethodsPatient Reported Outcome Measures data linked to NHS Hospital Episode Statistics in England in 2011/12 were used to analyse the association between market concentration of hospitals measured by the Herfindahl-Hirschman Index (HHI) and health gains for 337 hospitals.ResultsThe association between market concentration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
2
17
0
1
Order By: Relevance
“… 58 Studies across other specialties have shown mixed results for the effect of fixed-price markets on improvements in health-care quality. 8 , 23 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 …”
Section: Discussionmentioning
confidence: 99%
“… 58 Studies across other specialties have shown mixed results for the effect of fixed-price markets on improvements in health-care quality. 8 , 23 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 …”
Section: Discussionmentioning
confidence: 99%
“…The experience of the UK has suggested that, in a quasi-market, increased competition can, under certain circumstances, lead to increased quality without increasing costs (Gaynor et al, 2010). However, this proposition does not seem to hold generally (Feng et al, 2014;Gravelle et al, 2012). Somewhat similarly, private competitive markets in the US seem to reduce costs without sacrificing quality.…”
Section: 4mentioning
confidence: 97%
“…Kansainvälisessä kirjallisuudessa sähköisten potilaskertomusten tietojärjestelmien keskittyneisyyttä ja sen voimakkuutta on kuvattu Herfindahl-Hirschmanindeksillä (HHI) [29] muiden muassa Yhdysvalloissa [30], Iso-Britanniassa [31] ja Koreassa [32].…”
Section: 32019unclassified